2022
DOI: 10.3390/ijerph192113918
|View full text |Cite
|
Sign up to set email alerts
|

Justified Concerns? An Exploration of the Leg Tuck in a Tactical Population

Abstract: The leg tuck was replaced by the plank in the Army Combat Fitness Test, in part because it was felt it discriminated against women. There is limited leg tuck research, including between-sex comparisons and relationships with other fitness tests. This study investigated the leg tuck in a firefighter trainee population (274 males, 31 females). Archival fitness test data included: Illinois agility test (IAT); push-ups; pull-ups; leg tucks; multistage fitness test; 4.54 kg backwards overhead medicine ball throw (B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
23
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

5
0

Authors

Journals

citations
Cited by 6 publications
(24 citation statements)
references
References 51 publications
1
23
0
Order By: Relevance
“…What could influence these data are the between-sex differences in upper-body strength (10) and body composition (22) that have been documented in the literature. This is supported by Lockie et al (17) who found male firefighter trainees completed more leg tucks (∼13 repetitions) than females (∼6 repetitions). Lockie et al (17) noted the importance of upper-body pulling strength for this task by identifying a significant relationship between the pull-up and leg tuck ( r = 0.749).…”
Section: Introductionsupporting
confidence: 57%
See 1 more Smart Citation
“…What could influence these data are the between-sex differences in upper-body strength (10) and body composition (22) that have been documented in the literature. This is supported by Lockie et al (17) who found male firefighter trainees completed more leg tucks (∼13 repetitions) than females (∼6 repetitions). Lockie et al (17) noted the importance of upper-body pulling strength for this task by identifying a significant relationship between the pull-up and leg tuck ( r = 0.749).…”
Section: Introductionsupporting
confidence: 57%
“…Lockie et al (17) noted the importance of upper-body pulling strength for this task by identifying a significant relationship between the pull-up and leg tuck ( r = 0.749). In addition, grip strength, an indicator of total-body strength (30), has been suggested as being important for the leg tuck, given the need to support one's body mass while gripping the bar (17).…”
Section: Introductionmentioning
confidence: 99%
“…Because female soldiers were the primary group failing the leg tuck (more than 70% of enlisted women), Hardison et al [ 19 ] further stated that the leg tuck did not accurately measure their trunk strength because it also required upper body strength. This statement is partially supported by Lockie et al [ 51 ], who documented the significant relationship between the leg tucks and pull-ups ( r = 0.790, p < 0.001) in firefighters. Lockie et al [ 51 ], also showed large sex difference in leg tuck performance between male (12.64 ± 5.49 repetitions) and female (5.90 ± 5.01 repetitions) firefighters.…”
Section: Discussionmentioning
confidence: 53%
“…This statement is partially supported by Lockie et al [ 51 ], who documented the significant relationship between the leg tucks and pull-ups ( r = 0.790, p < 0.001) in firefighters. Lockie et al [ 51 ], also showed large sex difference in leg tuck performance between male (12.64 ± 5.49 repetitions) and female (5.90 ± 5.01 repetitions) firefighters. However, data from the present study show that performance in the leg tuck was strongly related with performance in the TFM, an essential combat task.…”
Section: Discussionmentioning
confidence: 53%
See 1 more Smart Citation